Pengaruh Karakteristik Individu, Beban Kerja dan Keterlibatan Kerja Terhadap Kinerja Pegawai - Adiguna, Irena Nesya (Universitas Sam Ratulangi, 2019)
This type of research is associative research using multiple linear regression data analysis techniques. The population in this study were all permanent employees at the Public Works and Spatial Planning Service as many as 272 samples taken using the Slovin formula to 73 respondents. The results of hypothesis testing indicate that individual characteristics, workload and work involvement together have a positive and significant effect on employee performance, individual characteristics partially influence employee performance while workload and work involvement partially do not affect employee performance at the Public Works Service And Spatial Planning of North Sulawesi ProvinceKeywords: Individual Characteristics, Workload, Work Involvement and Employee Performance